2016
DOI: 10.1007/s13592-016-0443-9
|View full text |Cite
|
Sign up to set email alerts
|

Distance between honey bee Apis mellifera colonies regulates populations of Varroa destructor at a landscape scale

Abstract: Inter-colony distance of Apis mellifera significantly affects colony numbers of the parasitic mite Varroa destructor. We set up 15 apiaries, each consisting of two colonies. Each apiary pair was assigned an inter-colony distance of 0, 10, or 100 m. Colonies were rendered nearly mite-free, then one colony in each pair was seeded with 300 female mites (mite-donor colony), while the other remained uninoculated (mite-recipient colony). After four months of monitoring, a whole model analysis showed that apiaries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 35 publications
2
53
1
Order By: Relevance
“…found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, 2015;DeGrandi-Hoffman et al, 2016;Peck et al, 2016;Nolan & Delaplane, 2017). The comparison of the genotypes of the foundress pairs suggested that the association of mites in a multiply infested cell is mainly driven by random choice rather than any specific adaptive behavior of the foundresses: mites neither with the same nor different genotypes preferentially coinvaded cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, 2015;DeGrandi-Hoffman et al, 2016;Peck et al, 2016;Nolan & Delaplane, 2017). The comparison of the genotypes of the foundress pairs suggested that the association of mites in a multiply infested cell is mainly driven by random choice rather than any specific adaptive behavior of the foundresses: mites neither with the same nor different genotypes preferentially coinvaded cells.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our AMOVA showed that the genetic variation between individual mites within colonies was most important while only very few differences were found in genotypic composition of mites among the five colonies. As the colony level had only very little influence on the population structure of the parasite, our results suggest that Varroa moves readily among hives at the apiary level, in accordance with other studies (Seeley & Smith, ; DeGrandi‐Hoffman et al ., ; Peck et al ., ; Nolan & Delaplane, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our models do not account for 307 landscape-scale movement of pathogens between apiaries. This is a phenomenon which has been 308 well documented (Lindström, Korpela, & Fries, 2008;Nolan & Delaplane, 2017). Given our results, 309 and empirical studies that did not find an association between colonies per apiary and disease risk 310 (Giacobino et al, 2014), we argue that increasing the number of colonies in an apiary does not 311 meaningfully alter within-apiary ecology to cause of increased disease prevalence.…”
Section: Resultssupporting
confidence: 47%
“…Our approach was informed by studies which have focussed on how changes in the number of colonies and apiary configurations (Jay, 1966(Jay, , 1968 alter drift (Dynes et al, 2017). Links between drift-mediated pathogen transmission and colony numbers have been documented for a variety of pathogens (Seeley & Smith, 2015)-including brood specialized and non-specialized, micro-and macro-parasites (Belloy et al, 2007;Budge et al, 2010;Dynes et al, 2017;Nolan & Delaplane, 2017). Larger numbers of colonies per apiary are a driver of higher drift (Currie & Jay, 1991), as are changes in apiary arrangement (Dynes et al, 2019;Jay, 1966).…”
Section: Discussionmentioning
confidence: 99%